Energy-saving Routing Algorithm Based on Cluster in WSN - He Ninghui; Li Hongsheng; Gao Jing (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
This paper takes the improved threshold formula and cluster radios formulas to choose cluster-heads by considering energy-saving, based on typical clustering routing protocol and optimal cluster-head selection formula. In the forming stage of cluster, the proportionality principle is used to make the distribution of cluster even more reasonable and during the stable stage of cluster, the member nodes in cluster use TDMA to communicate with the cluster-head node, and cluster-head nodes communicate with base station BS via multi-hop interrupt communication manner. Then it proposed the realization of target tracking based on the energy- saving routing algorithm. Finally, it can be seen in the simulation results that on the behalf of the network lifetime and average energy consumption, energy-saving routing algorithm is more reasonable. DOI: http://dx.doi.org/10.11591/telkomnika.v11i2.2032